1977
DOI: 10.1139/v77-484
|View full text |Cite
|
Sign up to set email alerts
|

Conformational study of a series of 6-substituted 5,6,7,12-tetrahydrodibenzo[a,d]-cyclooctenes by nuclear magnetic resonance spectroscopy

Abstract: Can. J. Chem. 55,3456 (1977). The conformational properties of seven 5,6,7,12-tetrahydrodibenzo[a,d]cyclooctenes bearing substituents at C-6 have been studied using variable temperature proton nmr spectroscopy. The position of the equilibrium between boat-chair (BC) and twist-boat (TB) conformers has been measured in several solvents. In contrast to the unsubstituted dibenzocyclooctene, appreciable amounts of TB conformer are present when C-6 is substituted by alkyl, hydroxy, or cyano substituents. Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The originally observed dependence for the geminal 2 J HCH coupling constant of the C( 12)-geminal protons in substituted 5,6,7,12-tetrahydrodibenzo [a,d]cyclooctenes with ring conformation [45][46][47][48] was extended to probe the conformation of 12Hdibenzo[d,g][1,3,2]dioxaphosphocins in solution. 6e,f,8a,b The observation of a geminal coupling constant of -12 to -13 Hz in 12H-dibenzo[d,g][1,3,2]dioxaphosphocins is consistent with a BC (or BB) conformation with the exocyclic substituent on phosphorus assuming a pseudoequatorial placement, whereas TB and B conformations were associated with coupling constants ranging from -14 to -19 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…The originally observed dependence for the geminal 2 J HCH coupling constant of the C( 12)-geminal protons in substituted 5,6,7,12-tetrahydrodibenzo [a,d]cyclooctenes with ring conformation [45][46][47][48] was extended to probe the conformation of 12Hdibenzo[d,g][1,3,2]dioxaphosphocins in solution. 6e,f,8a,b The observation of a geminal coupling constant of -12 to -13 Hz in 12H-dibenzo[d,g][1,3,2]dioxaphosphocins is consistent with a BC (or BB) conformation with the exocyclic substituent on phosphorus assuming a pseudoequatorial placement, whereas TB and B conformations were associated with coupling constants ranging from -14 to -19 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…1). In Scheme 2, a simplified transformation scheme of the eight-membered ring conformers of 3 is shown, which 13 and investigated by Arshinova and co-workers. 14 Because of the NOE effects 5b/1aЈ,bЈ > 5bЈ/1a,b, it is obvious that one of the phosphocine rings of 3 represents an equatorial boat-chair (e-BC) conformation with a 31 P NMR shift of 140.4 ppm for the 1Ј-P atom undergoing a fast conformational change to the axial distorted-twist-boat (a-DTB) conformation as indicated by the 4Ј,6Ј/1bЈ crosspeaks.…”
Section: Resultsmentioning
confidence: 99%
“…The 31 P NMR shifts were assigned by the 2D-31 P/ 1 H-HOESY and 1 H/ 31 P-HMBC methods, respectively. The 14-P atom of 4 gives a shift at 141.5 ppm, the Scheme 2 Conformational transformations of the two different thiaphosphocine fragments of the phosphorus thiacalixarene 3 according to Renaud et al 13 and the NOE effects observed (volume integrals A ij ).…”
Section: Resultsmentioning
confidence: 99%
“…The originally observed dependence of the magnitude of the couplings of the C(12) geminal protons in substituted 5,6,7,12-tetrahydrodibenzo[ a,d ]cyclooctenes upon ring conformation was extended to probe the conformation of 12 H -dibenzo[ d,g ][1,3,2]dioxaphosphocins in solution. The observation of a geminal coupling constant of −12 to −13 Hz with observable 5 J HP coupling of 2−4 Hz in 12 H -dibenzo[ d,g ][1,3,2]dioxaphosphocins is consistent with a BC conformation with the exocyclic substituent on phosphorus assuming a pseudoequatorial placement . Both the magnitude of the observed coupling constants and the observation of 5 J HP suggest that 7 and 8 assume a biased BC conformation in solution with a pseudoequatorial substituent on phosphorus.…”
Section: Resultsmentioning
confidence: 99%
“…38 The B conformation is characterized by a C aromatic -O-P-O torsion angle of 0°. 34 The originally observed dependence of the magnitude of the couplings of the C(12) geminal protons in substituted 5,6,7,12-tetrahydrodibenzo[a,d]cyclooctenes upon ring conformation [41][42][43][44] was extended to probe the conformation of 12H-dibenzo[d,g][1,3,2]dioxaphosphocins in solution. [34][35][36][37] The observation of a geminal coupling constant of -12 to -13 Hz with observable 5 J HP coupling of 2-4 Hz in 12H-dibenzo[d,g]-[1,3,2]dioxaphosphocins is consistent with a BC conformation with the exocyclic substituent on phosphorus assuming a pseudoequatorial placement.…”
Section: Resultsmentioning
confidence: 99%